2012
DOI: 10.1074/jbc.m112.357343
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Serine of Heterogeneous Nuclear Ribonucleoprotein L (hnRNP L) Mediates Depolarization-regulated Alternative Splicing of Potassium Channels

Abstract: Background: Excitable cells show activity-dependent alternative splicing of ion channels. Results: CaMKIV phosphorylates hnRNP L at Ser-513, which is essential for depolarization-repression of a Slo1 potassium channel exon and splicing factor U2AF65. Conclusion: Depolarization controls alternative splicing of Slo1 channels through Ser-513 phosphorylation and inhibition of U2AF65.Significance: This provides the first direct link between depolarization/CaMKIV and the constitutive spliceosome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 37 publications
2
75
0
1
Order By: Relevance
“…We also note the possibility that stimulation of T cells results in a posttranslational modification(s) of hnRNP L that alters its binding affinity and/or specificity. While such regulation of hnRNP L binding has not been reported in T cells, at least two reports have suggested that phosphorylation of hnRNP L in other cell types can alter its ability to recognize specific RNA target sequences (56,57). We emphasize, however, that less than 10% of the total binding events we detect for hnRNP L appear to be condition specific, and this number decreases further with increased stringency of peak calling (see Table S7 in the supplemental material).…”
Section: Discussionmentioning
confidence: 50%
“…We also note the possibility that stimulation of T cells results in a posttranslational modification(s) of hnRNP L that alters its binding affinity and/or specificity. While such regulation of hnRNP L binding has not been reported in T cells, at least two reports have suggested that phosphorylation of hnRNP L in other cell types can alter its ability to recognize specific RNA target sequences (56,57). We emphasize, however, that less than 10% of the total binding events we detect for hnRNP L appear to be condition specific, and this number decreases further with increased stringency of peak calling (see Table S7 in the supplemental material).…”
Section: Discussionmentioning
confidence: 50%
“…Membrane depolarization of cerebellar neurons induces phosphorylation of hnRNP L at Ser513 by CaMKIV, which enhances the interaction of hnRNP L with the CaMKIVresponsive RNA element (CaRRE1) upstream of STREX. As a result, U2AF binding is reduced and STREX is skipped (44). Second, histone hyperacetylation can cause up-regulation of specific splicing regulators at the transcription level, which will lead to either inclusion or skipping of their target alternative exons (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have found a CA-rich splicing regulatory element called CaRRE1 at this location (12)(13)(14)(15), suggesting relaxation of the constraint in some transcripts and the potential existence of other, similar elements. In particular, a purine-rich (Grich or A-rich) element such as a G tract at this location is expected to strongly disrupt the 3= splice site (3=SS).…”
mentioning
confidence: 80%
“…Immunodepletion of hnRNP H/F from a HeLa nuclear extract containing 0.5 M NaCl was carried out based on a published procedure (51). Immunodepleted HeLa nuclear extract was dialyzed 3 times against DG buffer (12) Purification of recombinant His-hnRNP H. To purify the recombinant N-terminal histidine-tagged hnRNP H, Escherichia coli Rosetta-gami 2 (DE3) pLysS (Novagen) bacteria transformed with pET28a-hnRNP H were grown overnight in LB medium containing 50 g/ml kanamycin and induced with 0.3 mM isopropyl 1-thio-␤-D-galactopyranoside at 37°C for 3 h. Protein purification was carried out as described previously (17) except that phosphate-buffered saline (PBS) was used instead of 50 mM Tris-HCl (pH 8.0) containing 0.1 M NaCl.…”
Section: Methodsmentioning
confidence: 99%